2016
DOI: 10.2217/nnm.15.219
|View full text |Cite|
|
Sign up to set email alerts
|

An Early Developmental Vertebrate Model for Nanomaterial Safety: Bridging Cell-Based and Mammalian Toxicity Assessment

Abstract: The results highlight the potential of Xenopus embryo analysis as a fast screening approach for toxicity assessment of NPs, which could be introduced for the routine testing of nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…The biological behavior of nanoparticles (NPs) is currently receiving much attention, in particular to enhance our understanding of any potential hazards involved in NP exposure and to optimize the use of nanotechnology in biomedical applications [ 1 3 ]. Most studies to date involve the use of cell cultures as a good model system that can provide in-depth mechanistic insight into the precise nature of how the cells interact with the engineered NPs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biological behavior of nanoparticles (NPs) is currently receiving much attention, in particular to enhance our understanding of any potential hazards involved in NP exposure and to optimize the use of nanotechnology in biomedical applications [ 1 3 ]. Most studies to date involve the use of cell cultures as a good model system that can provide in-depth mechanistic insight into the precise nature of how the cells interact with the engineered NPs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was shown that nanoparticle sizes above 200 nm had toxic effects. 21 Despite available literature on the effects of many Please do not adjust margins compounds on the larval development of X. laevis in environmental studies, there are only few reports evaluating nanoparticles toxicity and biodistribution designed for biomedical applications, 22,23 and there is still a lack of knowledge bridging biotransformation studies in cell-based assays with data generated from rodent in vivo systems.…”
Section: Introductionmentioning
confidence: 99%
“…embryos represent a valuable model to bridge in vitro and in vivo studies using mammals, with negligible ethical implications. To confirm this, a study by Webster and collaborators (Webster et al 2016) showed that after exposure to a range of NPs, the phenotypic score of Xenopus embryos showed a strong correlation with in vitro cell tests and, in particular, magnetite cored NPs, negative for toxicity in vitro and Xenopus, were further confirmed as nontoxic in mice.…”
Section: Discussionmentioning
confidence: 92%